Dissipation and Residues of Thiram in Potato and Soil - Shaowen Liu; Aijuan Bai; Li Zhou; Chuanshan Yu; Yanjie Li; Sufang Fan; Canping Pan (Journal of Chemistry)
The residue levels of thiram during potato cultivation in open field were evaluated. Thiram residues were determined by methylation derivation method with high performance liquid chromatography (HPLC). Wettable powder (WP) formulation containing 25% thiram was applied at 2320 g active gradient hm−2 (a.i. hm−2) dosage for the dissipation study. The decline rate in potato leave and soil followed first-order kinetics equation, and the half-life ranged from 2.8 to 5.4 days and 2.6 to 9.9 days, respectively. In terminal residue, the thiram was sprayed at 580 g a.i. hm−2 (low concentration, recommended dosage) and 1160 g a.i. hm−2 (high concentration, double of recommended dosage). The residues of thiram in potato and soil samples collected in the field at preharvest interval of 21 days and 30 days were all below 0.02 mg kg−1. The results show that thiram possesses low dietary risk in potato at harvest according to supervised residue field trial. It may be safe when used at recommended rate of application.